The Effectiveness of an Online Inquiry-Based Learning Environment towards Secondary School Students’ Behavioral Engagement and Performance in Science - Meng, Fangyuan; Jumaat, Nurul Farhana Binti (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The purpose of the current study is to examine the effectiveness of an online inquiry-based learning (IBL) environment on secondary school students’ behavioral engagement and performance in science. In this quasi-experimental design, 90 second year secondary school students from two classes in the Shandong Province region of China were recruited as participants. To gather the data, an online behavioral engagement questionnaire investigation and pre- and post-performance tests were administered to the experimental group (EG) and control group (CG) students. This study result shows that online IBL has a significant impact on secondary school students’ behavioral engagement and performance in science subjects.